Impact of multidisciplinary tumour board in the management of ovarian carcinoma in the first‐line setting. Exhaustive analysis from the Rhone‐Alpes region. (7th September 2020) - Ferraioli, Domenico; Bally, Olivia; Meeus, Pierre; Benayoun, David; Bakrin, Naoual; De Saint Hilaire, Pierre; Beal Ardisson, Dominique; Provençal, Jocelyne; Barletta, Hugues; Mousseau, Mireille; Chauleur, Céline; Verbaere, Sylvain; et al.
Abstract: Objective: Epithelial ovarian cancer (EOC) is a poor prognosis disease partly linked to diagnosis at an advanced stage. The quality of care management is a factor that needs to be explored, more specifically optimal organisation of first‐line treatment. Methods: A retrospective study, dealing with all patients diagnosed within the Rhone‐Alpes region with initial diagnosis EOC in 2012, was performed. The aim was to describe the impact of multidisciplinary tumour boards (MTB) in the organisation of care and the consequence on the patient's outcomes. Results: 271 EOC were analysed. 206 patients had an advanced EOC. Median progression‐free survival (PFS) is 17.8 months (CI95%, 14.6–21.2) for AOC. 157 patients (57.9%) had a front‐line surgery versus 114 patients (42.1%) interval debulking surgery. PFS for AOC patients with no residual disease is 24.3 months compared with 15.3 months for patients with residual disease ( p = .01). No macroscopic residual disease is more frequent in the patients discussed before surgery in MTB compared with patients not submitted before surgery (73% vs. 56.2%, p < .001). Conclusion: These results highlight the heterogeneity of medical practices in terms of front‐line surgery versus interval surgery, in the administration of neoadjuvant chemotherapy and in the setting of MTB discussion.